The Roles of School Operators in Managing Information Data as Guarantors of the Quality of Education Services - Mahsur, Mahsur (al-Afkar, Journal For Islamic Studies, 2024)
Quality management in education is a way of managing all directed educational resources so that everyone involved carries out their duties and participates in achieving academic goals. One of the supporting elements in the education unit is the academic staff; school operators are one of them. The lack of attention to school operators is the background of this research. The research method used is a descriptive method with a qualitative approach. The study was conducted at Pringgabaya District Middle School, East Lombok Regency. Collecting data in research is done by observation, interviews, and documentation. Informants in this study included: Principals, Teachers and Education Personnel (School Operators). The data analysis technique used is Miles and Huberman's interactive data analysis model. to measure the validity of the data in research conducted by triangulation. The study results show that apart from inputting and managing Dapodik, school operators also play an essential role in other data collection, from filling out e-reports and ARKAS to working on the PMP application. Besides that, the problem faced by school operators is a lack of attention to the performance and welfare of school operators, which can be seen from unclear regulations and legality.